STRATEGI METAKOGNITIF DALAM PEMBELAJARAN MATEMATIKA (Analisis Kuantitatif pada Siswa dan Guru Matematika MTs Pekanbaru) - mz, Zubaidah Amir (Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to investigate the use of metacognitive strategies in the learning of mathematics by students and teachers. The study population is students and teachers of mathematics Private MTs Al-Muttaqin accredited and MTs Al-Fajar Pekanbaru accredited B. Samples were eighth grade students and teachers in Mathematics at both school. Quantitative data collected through questionnaires given to students and teachers. The average student still seldom used metacognitive strategies in teaching mathematics with the average 2.73. So also for teachers, in general is still rarely use metacognition strategies, as seen from the average value of only 2.54. Strategy highest or frequently used by students in general are peer tutors averaging 3.1, and most rarely used were Evaluating the way of thinking and acting with the average of 2.4. Through the difference test (t-test) can be concluded that in general there is no difference in the use of metacognitive strategies in teaching mathematics at both school students. For teachers, the strategy most commonly used in mathematics learning is cooperative learning with the average 3.33, and most rarely use is to ask students berthink-aloud either by themselves or in pairs with the average value of 1.5 and 1.667. These findings contribute to reinforce the importance of training in mathematics learning metacognitive strategy, in particular think-aloud in a cooperative setting.